2015
DOI: 10.1016/j.molcel.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite DNA Lesion Recognition and Verification by XPC, TFIIH, and XPA in Nucleotide Excision Repair

Abstract: SUMMARY Transcription factor IIH (TFIIH) is essential for both transcription and nucleotide excision repair (NER). DNA lesions are initially detected by NER factors XPC and XPE or stalled RNA polymerases, but only bulky lesions are preferentially repaired by NER. To elucidate substrate specificity in NER, we have prepared homogeneous human ten-subunit TFIIH and its seven-subunit core (Core7) without the CAK module and show that bulky lesions in DNA inhibit the ATPase and helicase activities of both XPB and XPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 62 publications
(104 reference statements)
6
122
0
2
Order By: Relevance
“…These findings are consistent with the model that we previously suggested based on our data on archaeal XPD, in which XPD employs (simultaneously) a combination of different lesion-sensing approaches (concomitant with different strand preferences) to enhance its target spectrum (12). In support of our model, recent studies on the entire reconstituted human TFIIH complex also suggested recognition of strongly helix-distorting cisplatin as well as Cy3 adducts on the translocated strand (28). Based on crystallographic and biochemical data in combination with mutational analyses, a structural model has been suggested of how XPD interacts with DNA to recognize lesions (10,11,42).…”
Section: Uvrb and Xpd Helicase Activities Are Activated By Proteinsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with the model that we previously suggested based on our data on archaeal XPD, in which XPD employs (simultaneously) a combination of different lesion-sensing approaches (concomitant with different strand preferences) to enhance its target spectrum (12). In support of our model, recent studies on the entire reconstituted human TFIIH complex also suggested recognition of strongly helix-distorting cisplatin as well as Cy3 adducts on the translocated strand (28). Based on crystallographic and biochemical data in combination with mutational analyses, a structural model has been suggested of how XPD interacts with DNA to recognize lesions (10,11,42).…”
Section: Uvrb and Xpd Helicase Activities Are Activated By Proteinsupporting
confidence: 92%
“…In addition, bulky lesions (such as fluorescein, Cy3, or cisplatin adducts) may serve as mechanical roadblocks. Such lesions would hence directly hinder DNA translocation of the helicase leading to its stalling at the lesion site on the translocated DNA strand, as suggested previously for archaeal and human XPD (10,12,28). It is worth noting, however, that the diameter of the pore is too large to be blocked by typical bulky DNA lesions so that further interactions between the lesion and protein residues in the proximity of the pore are likely involved in specific lesion interactions.…”
Section: Uvrb and Xpd Helicase Activities Are Activated By Proteinmentioning
confidence: 87%
See 1 more Smart Citation
“…In both pathways, XPA is recruited to the damage site by the transcription factor II H (TFIIH) complex that is responsible for unwinding double-stranded DNA around the damaged nucleotide creating the NER bubble. XPA is generally understood to function in damage-verification and assembly of NER incision complexes 1,25-27 . XPA is recruited at the same time, and functions in coordination with, the eukaryotic ssDNA binding protein replication protein A (RPA).…”
Section: Introductionmentioning
confidence: 99%
“…XPA and XPC are important molecules involved in mediating nucleotide excision for DNA repair [22]. Yang et al [23] used polymerase chain reaction (PCR) to analyze the genomic DNA isolated from peripheral leukocytes collected from 501 ESCC patients and demonstrated that patients with the XPA 5′UTR A/G and XPC K939Q C/C genotypes are at higher risk of mortality after treatment than patients with wild-type homozygous genotypes, and this effect was more pronounced in patients treated with neoadjuvant CRT followed by esophagectomy.…”
Section: Negative Biomarkers In Blood Examinationmentioning
confidence: 99%